British nurses in Spain send news, "O.K. - Love" (press cutting) - Marchant, Hilde
041-0056-001 FRIDAY. DAILY EXPRESS MARCH 12, 1937 THE BOMBING GOES ON HILDE MARCHANT, Daily Express "Girl from Madrid," writes today of the men and women who left England voluntarily to tend the wounds inflicted on Spaniards by Spaniards. British Nurses In Spain Send News, "O.K. - Love" RAIDED DAILY FOR A WEEK: SILENCE ENDS CHEERFUL messages, written during an air raid and handed to Sefton Delmer, Daily Express Staff Reporter in Madrid, brought the first news in three weeks to relatives of the British Medical Corps in Spain. For six days their hospital, a meeting hall behind the Morata front, has been raided by bombers. No news came through — not even to medical headquarters at Albacete. Yesterday the Daily Express relayed "O.K., love," to the people waiting in England. Most of them expected bad news. "I suppose she is dead," were the first words of many. Then came relief. There was gusto and humour in most of the messages. The 'planes had passed. BACKBONE Yet for many weeks these twenty-four doctors and nurses have been the backbone of the medical service along the Morata - Valencia road. The attack has many times closed round them. In Valencia three weeks ago I met Dr. Murray Fullman, head of a party of six, first relief to the Morata Hospital. He said he had left an Oxford hospital to go home to see his mother in New York. He received a cable saying she was dead. He volunteered for Spain. Without knowledge of field or war surgery, he had brought some books with him to study. Now he attends 120 patients a day. He sent a message to Dr. Alexander Crawford and his wife, of Hendon, saying, "Doing famously." With Dr. Fullman were Dorothy Rutter and Joan Purser, in khaki, their medical kit slung over their shoulders. Dorothy Rutter told me her mother did not know she was out there. Her mother would worry, so she kept the trip to herself. 'VERY HAPPY' To her friends the Rev. E. William Mills and his wife, of Streatham, Dorothy says: "Well and very happy." They had not heard from her and were anxious. They promised to pass the message on to Mrs. Rutter, somewhere in Bournemouth. Joan Purser, ex-high school girl, member of the Croome Hunt, twenty-six-year-old daughter of a Worcestershire farmer, sent "Well and happy," to her parents. Mrs. Molly Murphy, of Hillside-gardens, Highgate, lively humorist of the corps, sent messages to her husband and son. She left them in January. Nurse in the great war, she felt her experience was needed. She is in charge of the wards, and wrote to her husband: " We arrived in an air raid — it has been going on ever since. I have a bed on the floor, a box for a pillow but I rarely have a chance to find how uncomfortable they are. I worked twenty-three hours, had a rest for three, went on to another fourteen hour duty. Stretcher cases queue at the door. We are usually too tired to sleep." She sent a cheery "Love . . . Mum." to her fourteen-year-old son taking his lessons in a Hampshire boarding school. JOKE AMID BOMBS "She'll make a joke even if she's being bombed," Mr. Murphy said when I relayed her message to him. " Bombed daily . . . alive and kicking." it said. Most of the girls who go out do not expect to return. They have said so. Fearless is twenty-five-year-old Phyllis Hibbert, trained nurse. whose mother said: "She wouldn't mind being bombed. She knew it was part of the work before she went. But she still wanted to go." Thora Silverthorne is the matron of the hospital. She is only twenty-five. Her mother, at Reading, said: " I had one letter to say she was working eighteen hours a day She was due for leave in January. On her way home she met another unit going out. They were under staffed, so she went back with them." The work of all these nurses is voluntary — their expenses and living are paid for. 'ALL'S WELL' Christopher Thornycroft, of Worthing, twenty-two-year-old student, left Oxford University in September, went to Spain with the Red Cross. He sent an "All's well" message to his parents, and added. "Have met Thora for the first time today." A happy, heroic little colony, these first words after a long silence gave some temporary release to the fears of their families. Yet the bombing around the hospital goes on.— H.M. THORA SILVERTHORNE, twenty-five, now hospital matron, with a patient CHRISTOPHER THORNYCROFT. From Oxford to war - and sock-washing, NURSE PURSER. From hunting-field to battle-field. NURSE RUTTER Well and very happy. NURSE MURPHY. Humorist in spite of bombs. 292/946/41/56